THE EFFECT OF IMPLEMENTATION AND SOCIALIZATION OF STANDARD OPERATIONAL PROCEDURES (SOP) FUND DISTRIBUTION ACTIVITIES WITH PARTNERS THAT RESULT IN INCOME GENERATING WHICH HAVE AN IMPACT ON FINANCIAL PERFORMANCE AT THE FACULTY OF SOCIAL AND POLITICAL SCIENCES SEMARANG STATE UNIVERSITY - Ariyati; rahmawati, Farida; Sanita Carolina Sasea (Forum Ilmu Sosial, 2025)
This research is intended to determine financial performance related to the implementation of Standard Operating Procedures (SOP) for disbursement of funds for activities that involve collaboration with income generating partners at the Faculty of Social and Political Sciences, Universitas Negeri Semarang (UNNES). The focus of the research is on the implementation of SOPs and socialization of SOPs by the Faculty of Social and Political Sciences UNNES finance department which processes the disbursement of funds to implementers, especially the Person in Charge of Activities regarding SOPs for disbursing funds for activities that involve collaboration with income generating partners at FISIP UNNES. The urgency of this research is to increase the understanding of all relevant parties, especially those responsible for activities, regarding the SOP for disbursing funds for activities that involve collaboration with partners that produce income generating so that financial performance, especially as measured by the disbursement of funds for collaborative activities with partners, can be carried out according to procedures, precisely. time, effective and efficient. This research uses a quantitative approach by testing the hypotheses that have been formulated. The data used in this research is primary data obtained from a survey by distributing questionnaires to those responsible for activities. Determination of the sample is based on what Hair ((Hair, 2009)) suggests, namely, 5 - 10 times the number of research indicators. In this study there were 21 indicators, so in this study the sample used was 105 people. The research period was carried out in 2024. The results of the research show that the implementation of SOPs and the socialization of SOPs for disbursing funds for activities that involve collaboration with income generating partners have a good or positive impact on the financial performance of the Faculty of Social and Political Sciences, Semarang State University, namely all parties, especially The person in charge of activities can carry out their duties well so that the process of disbursing funds for activities that involve collaboration with income generating partners carried out by the finance department can be carried out on time.